"She doesn't want to lose me": Experience of university-educated immigrants from the Philippines of communication and adaptation in the Icelandic labor market - Kristjánsdóttir, Erla S.; Christiansen, Þóra H. (School of Social Sciences, 2023)
The number of immigrants from the Philippines in Iceland has more than quadrupled in the past two decades. They are a visible minority in Iceland and their ethnicity, race, and nationality influences how they experience their position in the Icelandic labor market. In-depth interviews were conducted with highly-skilled immigrants from the Philippines working in Iceland. The objective was to develop an understanding of their lived experience of communication at work, their opportunities to contribute in the workplace, and how they are adapting to the workplace. Key findings support previous research that the Icelandic language is a major barrier to the integration of immigrants into the Icelandic labor market. They experience insecurity when they meet impatience and lack of understanding from their coworkers. As a visible minority they experience prejudice and cultural differences complicate conflict management. Despite being seen as perfect workers, few of the immigrants have sought promotions and their loyalty to their supervisor can hold them back. Integration is mutual, being able to keep their original culture and language and participate in the new culture, but the Filipinos in this study experience that they are solely responsible for the integration because immigration was their choice. Á síðustu tveimur áratugum hefur fjöldi Filippseyinga á Íslandi meira en fjórfaldast. Filippseyingar eru það sem kalla má „sýnilegur minnihlutahópur“ á Íslandi og hefur uppruni þeirra, kynþáttur og þjóðerni áhrif á upplifun þeirra af stöðu sinni á íslenskum vinnumarkaði. Tekin voru djúpviðtöl við háskólamenntaða innflytjendur frá Filippseyjum sem starfa á íslenskum vinnumarkaði. Markmið rannsóknarinnar var þríþætt: að öðlast skilning á hvernig Filippseyingar upplifa samskiptin á vinnustað, hvernig þeir meta möguleika sína á að leggja sitt af mörkum og hvernig þeim finnst þeim ganga að aðlagast að vinnustaðnum. Helstu niðurstöður styðja fyrri rannsóknir sem sýna að íslenskan er stór hindrun fyrir innflytjendur á íslenskum ...